Pengaruh Program “Muda Luar Biasa” Radio Suara Surabaya terhadap Minat Remaja dalam Berwirausaha - Galuh Dwi Kurniawati (Jurnal Spektrum Komunikasi, 2018)
Listening to radio is one of the entertainment media and also a means of information for the community. Radio programs that are listened to will affect everyday life for listeners, in searching for information and also entertainment. The development of mass media, which is quite rapid, has led to many new innovations from media companies. Several years ago many mass media were present in the new concept, believing that the presence of online media as a form of internet application. Radio is one form of mass communication, because what is made and produced by the media is addressed to the general public. The selection of Suara Surabaya radio can not be separated from the characteristics of the broadcast program that can be heard by various segments. This can be seen from the program at Radio Suara Surabaya, one of them is Muda Luar Biasa, the program is a forum for young people and young adults who have new ideas and ideas in various fields, so they can inspire their peers through Radio Suara Surabaya broader range. The purpose of this study is to find out how much influence the Young Extraordinary Radio Sound Surabaya program has on the interest of teenagers in entrepreneurship. The Use and Gratification theory is used in this study, the use of the theory because media users play an active role in selecting and using media in the media. In other words, media users are active parties in the communication process. The existence of a new idea or idea channeled through Radio Suara Surabaya's Extraordinary Young Program made this research relevant to the theory of Diffusion of Innovation, mentioned in the theory, a process of spreading new ideas or things in an effort to change a society.